A Look at Smallholder Cattle Farming in Payakumbuh, West Sumatra - Reswati; Aronal Arief Putra (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
The existence of smallholder cattle farming in Payakumbuh was studied. The research was conducted to obtain profiles of farmer demographics, cattle farming management, and reproductive performance. A survey was conducted in five sub-districts in Payakumbuh by interviewing 50 cattle farmers and conducting direct field observation. Smallholder farmers in Payakumbuh are typically an average of 45.02 years old, commonly senior high school graduates, occupied in the agricultural field with their own cattle ownership, experienced for 18.1 years, involved in cattle farming for additional income, and commonly focused on Simental crossbred raising. Cattle management was mainly categorized as good, as represented by feeding management (application of routine forage and concentrate, twice daily feeding frequency, and ad libitum drinking water), rearing (intensive rearing and natural weaning), housing (permanent housing structures, individual housing systems, and draw well water sources), and health (regular deworming). Reproductive performance (20.4 months age at first mating, 1.55 service per conception, 14.63-month calving interval, and 3.96 months for re-mating after calving) is also close to the ideal standard. To sum up, the presence of smallholder farmers is significant and could serve as a reference for farmers in other areas of West Sumatra. Enhancing applied technology is necessary to upgrade their cattle farming scale.